Formulation of Red Bean Meatballs as a Local Food Alternative: Increasing Protein and Fiber Using Design Expert D-Optimal - Yusnidar, Yusnidar; Kartika, Eti; Iqbal, Muhammad; Vitoekpon, Isaac; Husseini, Monir Mohamed El; Hagos, Habtamu; Khan, Younas (Journal of Educational Technology and Learning Creativity, 2023)
Purpose of the study: The purpose of this study was to produce an optimal red bean-based meatball formula using the Design Expert D-Optimal method, with a focus on increasing protein and fiber content and reducing fat content to support food diversification based on local ingredients. Methodology: The methodology of this study used red beans (Phaseolus vulgaris L.), Rose Brand cassava flour, and Segitiga Biru wheat flour. The tools included a Food Processor, digital scales, and texture analyzer. The analysis was carried out using the Kjeldahl method for protein, the Soxhlet method for fat, and Design Expert D-Optimal software was used for formula optimization. Main Findings: The main results of this study indicate that the optimal formula for red bean-based meatballs consists of 52% red beans, 18% cassava starch, and 11% wheat flour. This formula has the highest protein content of 15.50%, crude fiber content of 2.84%, and a chewy texture that is preferred by panelists. The attributes of color, taste, and aroma achieved the best hedonic value in the organoleptic test. Novelty/Originality of this study: The novelty of this research lies in the use of red beans as the main ingredient in making analog meatballs that are healthier, low in fat, and high in protein. In addition, the formula optimization method using Design Expert D-Optimal software provides a scientific approach to producing the best quality products, supporting local food diversification, and expanding the market potential of plant-based products in Indonesia